Vulnerability evaluation of fire prevention system of the University of Quindio (Revista de Investigaciones Universidad del Quindío, 2017)
The study proposes to evaluate the vulnerability of the fire protection system of the buildings of the University of Quindío following the requirements established in 2010 seen in the titles J "fire protection requirements in buildings" and K "Additional requirements" of Colombia Earthquake Resistant Standards. According to the result of the evaluation, alternative solutions are defined to use. In addition, the evaluation procedures implemented to measure the status and capacity of action of an institution of higher education is presented according to the characteristics of its buildings.
Keywords: Fire protection system; building vulnerability; title J & K; NSR 2010; campus